HUBUNGAN ANTARA ASI EKSKLUSIF DENGAN PERKEMBANGAN BAYI USIA 6-12 BULAN - Susilowati, Virgin; Ratna, Ratna (Jurnal Kebidanan, 2024)
Child’s development in the early of life will effect children wellbeing in the future. Early child development will be optimal if their nutritional need has been fullfiled. Breast Milk is the best food for baby in their early life. The purpose of this research was to know the association between duration of breast feeding with baby development age 6-12th month in Puskesmas Jambon work area district Ponorogo. This study was quantitative researches with cross sectional design which was done to 141 baby age 6-12th month in Puskesmas jambon work area. The result of this study was 47,5% baby who was not receiving exclusive breast feeding suspected had delayed developmental status, 26,2% baby who had been exclusively breast feeding for 6 month suspected had delayed developmental. Statistical analyze with logistic regression showed there are positif correlation between nutrional status with baby’s development p=0,020. Baby who was not exclusively breast feeding until 6-month 2,5 time higher to have delayed development (95% CI 1,158-5,308).